Sexual Violence in The Miseries and the Misfortunes of War by Jacques Callot (1633) - Knowles, Marika Takanishi (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
The Miseries and the Misfortunes of War (1633) by Jacques Callot is one of the most significant artistic reflections on multiple, fracturing military conflicts in seventeenth-century Europe. In this series of eighteen etchings, the question of wartime sexual violence arises as a part of Callot’s engagement with the subject of pillaging soldiers. This is the only time in Callot’s oeuvre that he represents rape; it is also the only time that he represents a domestic interior. As this article argues, Callot’s representation of wartime rape reflects increasingly intertwined conceptualizations of the household and female sexuality—and its potential violation.